2009
DOI: 10.1007/s10681-009-0052-z
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of aphid vector and genetic tolerance to infection by potyvirus in hot pepper

Abstract: The productivity and marketable quality of hot pepper (Capsicum annuum var. annuum L.) are low in tropical regions mainly due to virus infections and lack of effective virus management strategies. The absence of effective virus management strategies could be attributed to lack of information on virus vectors and host resistance. Parental (P 1 and P 2 ) and progeny (F 1 , B 1 , B 2 and F 2 ) generations of five hot pepper crosses were grown in Ethiopia at three sites (Bako, Hawasa and Melkasa) to monitor number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Starting 20 days after transplanting, all pepper plants in each plot were visually assessed for the incidence of EPMV infection caused by natural infestation special aphid's infestation. Well established symptoms based evaluation method for EPMV was used for rating of the incidences [8,15]. Ethiopia pepper mottle virus incidence on each experimental treatment was recorded by counting number of diseased plants and calculating as the proportion of the diseased plant over the total number of stand count per treatment.…”
Section: Incidence Of Ethiopian Pepper Mottle Virus (Epmv)mentioning
confidence: 99%
“…Starting 20 days after transplanting, all pepper plants in each plot were visually assessed for the incidence of EPMV infection caused by natural infestation special aphid's infestation. Well established symptoms based evaluation method for EPMV was used for rating of the incidences [8,15]. Ethiopia pepper mottle virus incidence on each experimental treatment was recorded by counting number of diseased plants and calculating as the proportion of the diseased plant over the total number of stand count per treatment.…”
Section: Incidence Of Ethiopian Pepper Mottle Virus (Epmv)mentioning
confidence: 99%
“…In Picardie, a region located in the northern part of France, a Þeld survey of miscanthus crops was conducted in 2011 (29 AprilÐ29 July). Yellow water traps were placed on a pole at a height of 50 cm above the canopy and 50 m from the border to attract and collect insects ßying over the Þelds (according to the protocol detailed in Marame et al 2010). Collected data showed that all the common aphid species occurring throughout northern France on many crop plants were present.…”
mentioning
confidence: 99%